Pengaruh Usia Sumber Daya Manusia pada Efektivitas Kinerja Koperasi di Era Revolusi Industri 4.0 - Nurul Maulina, Meisya; Rizaldi, Arjuna (Transpublika Publisher, 2021)
The era of the Industrial Revolution 4.0 is dubbed the era of digitalization. All data will be interconnected by technology. This causes the age range of human resources to affect the effectiveness of cooperative work. Millennials have an innovative and creative mindset. Utilization of modern information technology must be supported by competent human resources. Competent human resources will create a good cooperative. The purpose of this study was to determine the effect of cooperative resource age in the era of the industrial revolution 4.0 and to determine the quality of cooperative human resources needed in the era of the industrial revolution 4.0. This research formulates the problem of why the age of cooperative resources has an effect on the era of the industrial revolution 4.0 and the quality of cooperative human resources needed in the era of the industrial revolution 4.0. Data collection techniques were obtained from electronic literature, books, journals, articles, and other sources. The results of the study show that the age of human resources has an influence on cooperatives in the industrial era 4.0 because the skills needed in this era are owned by the millennial generation. Keywords: Cooperatives, Human Resources, Technology, Age and Quality